Salt Reduction In Salted Fish By Boiling And Soaking In Hot Water - Rahmatia Misro; Silvana Dinaintang Harikedua; Engel Victor Pandey; Helen Jenny Lohoo; Josefa Teti Kaparang; Daisy Monica Makapedua (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2022)
Salted fish is one of the fishery products that have the potential to be developed because many fishery products are preserved by salting. The unique characteristics of this salted fish mainly lie in its distinctive taste, aroma, and texture. Consumption of food products with high salt content can trigger the emergence of degenerative diseases such as hypertension, cardiovascular and stroke. This study aims to find an alternative to reducing salt content in salted fish and to determine the salt content, water content, and total fungi in salted fish after boiling and soaking in hot water at different times (10 and 20 minutes). The results showed that the maximum reduction in salt content occurred in the boiling treatment for 10 minutes, which was about 43.5% of the initial salt content. Furthermore, the water content of salted fish after undergoing treatment of boiling and soaking time does not meet the standard of SNI 8273:2016 which is in the range of 50.3 – 58.8%. The total fungi test results showed that the boiling and soaking treatment with hot water could reduce the number of molds in salted fish. Keywords: Keywords: Salted Fish, Boiling, Soaking, Salt reduction.   Abstrak Ikan asin merupakan salah satu produk perikanan yang potensial dikembangkan dikarenakan sekitar banyak produk perikanan mengalami pengawetan dengan cara digarami. Daya tarik ikan asin ini terutama terletak pada citarasa, aroma dan tekstur yang khas. Konsumsi produk pangan dengan kadar garam yang tinggi dapat menjadi pemicu munculnya penyakit degeneratif seperti hipertensi, kardiovaskuler dan stroke. Penelitian ini bertujuan untuk menemukan alternatif pengurangan kadar garam pada ikan asin dan untuk mengetahui kadar garam, kadar air, dan total kapang pada ikan asin setelah perlakuan perebusan dan perendaman dengan air panas dengan waktu yang berbeda (10 dan 20 menit). Hasil penelitian menunjukkan bahwa pengurangan kadar garam maksimal terjadi pada perlakuan perebusan selama 10 menit yaitu sekitar 43.5% dari kadar garam awal. Selanjutnya, kadar air ikan asin setelah mengalami perlakuan waktu perebusan dan perendaman sudah tidak memenuhi standar SNI 8273:2016 yaitu berada pada kisaran 50,3 – 58.8 %. Hasil uji total kapang memperlihatkan bahwa perlakuan perebusan dan perendaman dengan air panas dapat mereduksi jumlah kapang pada ikan asin. Kata Kunci : Ikan Asin, Perebusan, Perendaman, Reduksi Garam